2014
DOI: 10.1016/j.ophtha.2014.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Nocturnal Systemic Hypotension Increases the Risk of Glaucoma Progression

Abstract: Objective The objective of this prospective, longitudinal study of patients with normal-tension glaucoma (NTG) was to determine whether patients with nocturnal hypotension are at greater risk for visual field (VF) loss over 12 months than those without nocturnal hypotension. Design Prospective, longitudinal study. Participants Consecutive patients with NTG with at least 5 prior VF tests were screened for eligibility. Methods The baseline evaluation assessed demographic and clinical characteristics, cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
1
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(89 citation statements)
references
References 46 publications
2
82
1
4
Order By: Relevance
“…This result is reasonable, as the aforementioned changes in pressure will reduce the overall perfusion pressure of the LC. It has also been shown that both an increase in central venous pressure and a decrease in arterial pressure are risk factors for the development of OAG, [49][50][51][52] and our result suggests that changes in blood pressure can significantly impact LC hemodynamics and potentially contribute to OAG progression.…”
Section: Discussionsupporting
confidence: 65%
“…This result is reasonable, as the aforementioned changes in pressure will reduce the overall perfusion pressure of the LC. It has also been shown that both an increase in central venous pressure and a decrease in arterial pressure are risk factors for the development of OAG, [49][50][51][52] and our result suggests that changes in blood pressure can significantly impact LC hemodynamics and potentially contribute to OAG progression.…”
Section: Discussionsupporting
confidence: 65%
“…These results are supported by clinical observations. Low blood pressure (i.e., arterial hypotension) is associated with low perfusion of ocular tissues (Caprioli and Coleman 2010;Pournaras et al 2008) and is identified as a risk factor for many ocular diseases, including glaucoma (Charlson et al 2014;Costa et al 2014;Deokule and Weinreb 2008;He et al 2011) and nonarteritic anterior ischemic optic neuropathy (NAION) (Hayreh 2008;Kerr et al 2009). High blood pressure (i.e., arterial hypertension) is also an important clinical condition and has been identified as a risk factor for retinal artery and vein occlusion and macular edema (Bhargava et al 2012;Kida et al 2014;Kolar 2014;Martinez et al 2014), diabetic retinopathy (Bhargava et al 2012;Wong and Mitchell 2007) and NAION (Bawazir et al 2011).…”
Section: Simulation Results In Baseline Conditionsmentioning
confidence: 99%
“…[3][4][5][6] Decreased retinal perfusion has also been demonstrated angiographically in glaucoma patients using fluorescein angiography. [7][8][9][10] These findings has raised the interest in the potential role of decreased ocular perfusion as an etiopathogenic factor for the glaucomatous optic neuropathy (GON), together with epidemiologic or clinical data that demonstrated the association of low blood pressure [11][12][13] or nocturnal blood pressure dips [14][15][16] with glaucoma. In contrast, Quigley et al 17 demonstrated that the density of capillaries remained constant across a wide range of neural tissue losses within the optic nerve head (ONH) in both experimental and human glaucoma eyes.…”
mentioning
confidence: 99%